2014
DOI: 10.5539/sar.v3n1p67
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Dockounou Manufacturing Process Parameters

Abstract: <p>The present study aimed to determine optimum values of the process factors to obtain a standard method of preparation with best quality of dockounou.</p> <p>Several samples of dockounou were prepared with different proportions (75 to 95%) of senescent plantain, cooking time, fermentation time and temperature of oven. Sensorial characteristics of the samples were investigated. Optimal values (scores) of both boiled and baked dockounou prepared with maize or rice flour were identified throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Consumers seemed to prefer products containing 15 and 17.5% flour irrespective of the flour type. This seem to confirm the consumer preference of 15% maize flour inclusion for optimised dockounou, lower than the 10% inclusion of rice flour for optimised product reported by Edwige et al (2014). The appearance, external/crust colour, internal colour, hardness, aroma and sweetness, contributed significantly to the overall differences among the products.…”
Section: Principal Component Analysissupporting
confidence: 51%
See 1 more Smart Citation
“…Consumers seemed to prefer products containing 15 and 17.5% flour irrespective of the flour type. This seem to confirm the consumer preference of 15% maize flour inclusion for optimised dockounou, lower than the 10% inclusion of rice flour for optimised product reported by Edwige et al (2014). The appearance, external/crust colour, internal colour, hardness, aroma and sweetness, contributed significantly to the overall differences among the products.…”
Section: Principal Component Analysissupporting
confidence: 51%
“…The overall acceptability of the kaakle prepared with the inclusion of 20% flour was good. However, Edwige et al (2014) reported between 10 and 15%, to be the acceptable levels for rice and maize flours in the formulation of both optimised steamed and baked dockounou (an Ivorian derivative of ofam).…”
Section: Effect Of Flour Concentrations On Sensory Acceptability Of Ofammentioning
confidence: 99%
“…These transformations include different preparation methods such as frying, boiling, roasting, pounding, boiling and steaming [10,1]. In its senescent state, plantain is used in the preparation of many local dishes or snacks [1] in which the most common are claclo, m'bahou, dockounou and apity [11,12]. However, in some regions of Côte d'Ivoire, particularly in Gontougo, senescent ripe plantain pulp is dried in the sun to produce a food product called "Tanga".…”
Section: Introductionmentioning
confidence: 99%